2014
DOI: 10.21307/sjcapp-2015-006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment of Identity Pathology During Adolescence

Abstract: Personality disorders can be seen as patterns of maladaptive personality traits that have their onset during childhood or adolescence and that have an impact on the individual throughout the life span. Identity disturbance is seen as the central construct for detecting severe personality pathology-and, most notably, borderline personality disorder-in adults and adolescents. Therefore, in the revision of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, the construct of "identity" has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
8
0
4
Order By: Relevance
“…Thus, we would argue that current treatments available for adolescents with NSSI and D-BPP (e.g. DBT-A [43], MBT [44], or Adolescent Identity Treatment, AIT) [50] should evaluate their interventions using personality functioning and associated pathology as primary treatment targets and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we would argue that current treatments available for adolescents with NSSI and D-BPP (e.g. DBT-A [43], MBT [44], or Adolescent Identity Treatment, AIT) [50] should evaluate their interventions using personality functioning and associated pathology as primary treatment targets and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Jung i sur. (29) su ispitali razlike u razvoju identiteta kod adolescenata s različitim psihičkim poremećajima pomoću upitnika AIDA (30,31). Istraživanje Junga i sur.…”
Section: Discussionunclassified
“…Jung et al (29) examined differences in identity development between adolescents with different psychiatric disorders using the AIDA questionnaire (30,31). Jung et al (29) found that patients with personality disorders, mostly borderline or other B cluster personality disorders scored on all AIDA scales remarkably higher than the healthy norm population, and higher than the other patient groups with internalising or externalising disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Relacionado con los problemas en su conformación, el constructo "difusión de identidad", derivado de la teoría del desarrollo identitario de Erikson (1956), se caracteriza por dificultades en el logro de la intimidad, la elección de carrera, la capacidad para la competencia y para el logro de una autodefinición psicosocial, acompañado de un sentimiento de aislamiento y vacío interno. Esta definición concuerda con síntomas típicos del TLP como el vacío crónico, superficialidad, poca tolerancia a la ansiedad, dificultad en el control de impulsos y en el logro de una autodefinición estable, además de problemas en el establecimiento de relaciones de intimidad (Schlüter-Müller, Goth, Jung, & Schmeck, 2015). Becker, Grilo, Edell, y McGlashan (2002), explorando una muestra clínica de adolescentes a través de entrevistas semiestructuradas, encuentran que la alteración de la identidad en conjunto con ira incontrolable y desregulación afectiva son los síntomas más significativos para el diagnóstico adecuado del trastorno límite de la personalidad en los adolescentes.…”
Section: Introductionunclassified
“…El logro de una identidad estable y coherente es una tarea propia del desarrollo de un adolescente. Una identidad difusa en esta etapa emerge como fenómeno psicopatológico distinguible de la crisis de identidad normativa, y ha sido vinculada a patología de la personalidad (Fonagy et al, 2015;Schlüter-Müller et al, 2015;Westen, Betan, & DeFife, 2011). Esto la convierte en un constructo de interés clínico y una oportunidad para intervenir precozmente en la emergencia del TLP, realizando acciones enfocadas en los procesos de mentalización y su repercusión en la consolidación de la identidad de los adolescentes, en una ventana de tiempo en la que en que se amplía y se complejiza su mundo interpersonal (Blakemore, 2012).…”
Section: Introductionunclassified